(untitled) (Международный научный журнал «Инженер», 2026)
The seismic strength or resistance of underground structures mainly depends on the forces of their interaction with the surrounding soil. These interaction forces are governed by specific laws. The simplest law includes an interaction coefficient, which is the primary parameter. The values of this coefficient are determined experimentally. For underground metro structures, experimentally determining the interaction coefficient under dynamic (seismic) loads is a highly challenging problem. This paper suggests a straightforward method to estimate interaction parameters, including the interaction coefficient, based on the strength characteristics of the soil surrounding underground metro structures.